Digital Transformation Strategy to Enhance Consumer Trust in Apple Cider Vinegar Products through Quality, Legality, and Digital Education - Renaldo, Nicholas; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Panjaitan, Harry Patuan; Purnama, Intan; Jahrizal, Jahrizal; Yovita, Indri; Veronica, Kristy; Musa, Sulaiman; Wahid, Nabila (First Ciera Publisher, 2024)
The increasing popularity of Apple Cider Vinegar (ACV) as a health supplement has created opportunities for Micro, Small, and Medium Enterprises (MSMEs) in the health product market. However, issues such as exaggerated health claims, inconsistent product quality, lack of regulatory certifications, and insufficient consumer education have contributed to declining trust among digital consumers. This study explores how digital transformation can enhance consumer trust in ACV products through a qualitative approach involving in-depth interviews with ACV producers and digital content analysis. The findings reveal that many producers lack standardization in quality control, face challenges in obtaining legal certification (BPOM, halal), and underutilize digital platforms for health education. As a solution, the study proposes a strategic framework based on a digitally adapted Business Model Canvas, which integrates transparent product labeling, educational digital content, and trust signals such as verified reviews and interactive consumer engagement. This digital strategy not only strengthens brand credibility but also addresses health risks associated with improper ACV use, promoting safer and more informed consumption. The research contributes to the literature on digital business strategies for functional health products and provides a practical roadmap for MSMEs to build consumer trust through quality, legality, and education.